KARAKTERISTIK PESERTA DIDIK IDEAL DALAM TINJAUAN AL-QUR’AN - Al Muhlasin, Yafie; Tobroni, Ahmad Yusam (Institut PTIQ Jakarta, 2022)
To be able to have good characteristics for students, it must first be based on good qualities (characters) that are ideal in a review of the Qur'an. Because in the Qur'an emphasizes the importance of the existence of students in terms of education (study). The purpose of this study was to determine the characteristics of ideal learners in the review of the Qur'an. This research uses a qualitative approach (library research) with the Qur'an as the source. Characteristics of students can be seen from the indicators of their characteristics, namely the abilities, values, attitudes, and interests of the students. From these indicators, it can be seen from the arguments of the Qur'an that discuss these indicators, so that a student can have ideal characteristics according to the Qur'an. First, students must be able to develop and preserve their potential given by God from birth. Second, students must be able to build comfort with the surrounding environment. Third, students must be able to do the attitudes that please God. Fourth, students must be able to intend to study seriously because of their willingness to be able to do it